1999
DOI: 10.1142/s0218127499001024
|View full text |Cite
|
Sign up to set email alerts
|

Yet Another Chaotic Attractor

Abstract: This Letter reports the finding of a new chaotic at tractor in a simple three-dimensional autonomous system, which resembles some familiar features from both the Lorenz and Rossler at tractors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
938
0
10

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 2,490 publications
(951 citation statements)
references
References 2 publications
3
938
0
10
Order By: Relevance
“…Here, as an example, we state our results for the polynomial differential system in R 3 ,ẋ = a 1 x + a 2 y,ẏ = a 3 x + a 4 y + a 5 xz,ż = a 6 xy + a 7 z, see Example 3.5 in Section 3. It includes the Lorenz system [26], the Lü system [27] and the Chen system [6], and its Darboux integrability has been studied in [25,23,28], respectively. The differential system studied in [39] also belongs to this family.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Here, as an example, we state our results for the polynomial differential system in R 3 ,ẋ = a 1 x + a 2 y,ẏ = a 3 x + a 4 y + a 5 xz,ż = a 6 xy + a 7 z, see Example 3.5 in Section 3. It includes the Lorenz system [26], the Lü system [27] and the Chen system [6], and its Darboux integrability has been studied in [25,23,28], respectively. The differential system studied in [39] also belongs to this family.…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…is generated by iterating Lorenz [75] and Chen [35] Systems and doing some postprocessing on all the variables of state. When a variation of stream cipher is created, as in the case under study, obtaining the keystream is totally equivalent to obtaining the key whenever different plain-images are encrypted using the same key.…”
Section: • Masking Proceduresmentioning
confidence: 99%
“…This cryptosystem is intended to encrypt images through the concatenation of a shuffling and masking procedures. The shuffling procedure is based on the iteration of the logistic map, whereas masking is built upon the iteration of two continuous-time chaotic systems: Lorenz [75] and Chen Systems [35]. The Lorenz System is given by…”
Section: Case Study 826 ([28])mentioning
confidence: 99%
“…Since a description of the general case is rather messy and uneasy, at least notationally, to facilitate the description and discussion, we use a specific chaotic system as an example. This system is still not too special, in the sense that it unifies both the Lorenz [2] and the Chen systems [9,10], where the latter is the dual system of the former in a sense defined in [11]: The Lorenz system satisfies the condition a 12 a 21 > 0 while the Chen system satisfies a 12 a 21 < 0, where A ¼ ½a ij 3Â3 are the matrix of the linear part of the chaotic systems. Recently, L€ u u et al [12][13][14] found a unified chaotic system that not only includes the case of a 12 a 21 ¼ 0 [12] but also the Lorenz and Chen systems as two extreme cases.…”
Section: The Problem Formulationmentioning
confidence: 99%